Síndrome febril indeterminado y paniculitis: un caso raro de linfoma subcutáneo de células T similar a paniculitis - José Leite; José Cardoso; José Almeida; Daniela Marado (Sociedade Galega de Medicina Interna, 2021)
Subcutaneous panniculitis-like T-cell lymphoma (SPTCL) is an extremely rare form of skin lymphoma that primarily involves subcutaneous adipose tissue. SPTCL diagnosis is demanding because of its nonspecific systemic features, such as fever or weight loss, that usually mimic other more common conditions. Further complicating diagnosis, lesion biopsies are often inconclusive. For this matter, patients are frequently seen by different clinicians and may be submitted to various cutaneous biopsies before a definitive diagnosis is reached. We present the case of a 64-year-old man with a two-month history of fever and subcutaneous nodular lesions scattered by the lower limbs and torso, whose final diagnosis of SPTCL illustrates the main features of the disease as well as the challenge of its identification.